2002
DOI: 10.1128/aac.46.6.1695-1703.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Fluconazole Resistance in Candida dubliniensis Isolates from Human Immunodeficiency Virus-Infected Patients with Oropharyngeal Candidiasis

Abstract: Candida dubliniensis is a newly identified species of Candida that is phenotypically similar to but genetically distinct from C. albicans. This organism has been recovered with increasing frequency from the oral cavities of human immunodeficiency virus (HIV)-infected and AIDS patients and has been implicated as a causative agent of oral candidiasis and systemic disease. In the present study we characterized the molecular mechanisms of resistance to fluconazole (FLC) in C. dubliniensis clinical isolates from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 40 publications
3
76
0
Order By: Relevance
“…Transcriptional upregulation of multidrug transporter genes has frequently been identified in C. glabrata (Vermitsky & Edlind, 2004), other Candida species (Katiyar & Edlind, 2001;Perea et al, 2002) and nonCandida yeasts (Posteraro et al, 2003). In this investigation, we isolated the total proteins, not just the drug-resistant proteins.…”
Section: Azole Resistance and Morphologically Variable Mutantsmentioning
confidence: 99%
“…Transcriptional upregulation of multidrug transporter genes has frequently been identified in C. glabrata (Vermitsky & Edlind, 2004), other Candida species (Katiyar & Edlind, 2001;Perea et al, 2002) and nonCandida yeasts (Posteraro et al, 2003). In this investigation, we isolated the total proteins, not just the drug-resistant proteins.…”
Section: Azole Resistance and Morphologically Variable Mutantsmentioning
confidence: 99%
“…Up-regulation of CdCDR1 has been observed in fluconazole-resistant clinical isolates of C. dubliniensis and in-vitrogenerated derivatives [31,38]. However, Moran et al [40] have shown that, while CdCdr1p is important for mediating reduced susceptibility to itraconazole and ketoconazole, it is not required for fluconazole resistance in isolates that exhibit increased CdMDR1 expression.…”
Section: Mechanisms Of Azole Resistance In C Dubliniensismentioning
confidence: 99%
“…While most isolates of C. dubliniensis are susceptible to fluconazole, a number of isolates exhibiting either decreased susceptibility (8 µg/ml MIC 32 µg/ml) or resistance (MIC 64 µg/ml) to fluconazole have been described [12,20,21,[28][29][30][31][32]. These isolates were mostly recovered from HIV-infected patients receiving fluconazole therapy.…”
Section: Azole Susceptibility In C Dubliniensismentioning
confidence: 99%
See 1 more Smart Citation
“…Ketoconazole (KCZ) is widely used in the treatment of superficial mycoses. Nevertheless, azole resistance and cross-resistance have been documented in clinical Candida species [3,4] . Despite continuous expansion in the arsenal of antifungal drugs, antifungal drugs available cannot meet the increasing requirements for managing infections in medically complex patients.…”
Section: Introductionmentioning
confidence: 99%